EVALUASI PENGEMBANGAN EKOWISATA DI KAWASAN TAHURA NGURAH RAI - WAHYUNI, PUTU IKA; ARDHANA, IPG; SUNARTA, I NYOMAN (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2012)
Since January 1992 MIC has initiate Tahura Ngurah Rai are as a ecotourism area, offering programs such as : Mangrove Education Tour & Tracking, Bird Watching; Finishing; Mangrove Tree Plantation or Adoption, Canoeing, and Boating programs. However, its growth has not me the management’s targets in term of the number of visitors, improved facilities available, and the surrounding Tahura are – especially its cleanliness-these are far from expectation standard. The evaluation of eco-tourism area of Tahura is aimed at understanding the profile of the eco-tourism area and to understand to what extent the ecotourism has met criteria/principles issued in the national workshop. This ecotourism will offer recommendations designed in relation to programs that has not been working so far after identifying obstacles of their implementation. The method used in the evaluation of this eco-tourism area I descriptive analysis by analyzing interview data, observations, and literature studies. These descriptive data then are measured against criteria and principles of national eco-tourism. Since March 12, 2007 Mangrove forest area is under the management of BPHM-wil-I continuing JICA IC program. Facilities available in the area are as follows; Wood Trails, 5 Huts along the trail, Floating Decks, 2 Viewing Towers; MIC/BPHM Office Building, Touch Pools, Seeding area, and a Monitor Pool. These facilities right now are still in good condition and can be used to implement the eco-tourism programs. From the 6 programs offered, the Mangrove Education Tour & Tracking Program gets the most interests from visitors than the other 5 programs. From 9 criteria used to evaluate the programs, the outcome is as follows: 1) Being sensitive to and respecting socio-cultural values and religious tradition of local community (88% met); 2) Showing concern, commitment, and responsibility to natural conservation and cultural heritage (95,24% met); 3) Provide interpretation that facilities visitors to enjoy nature and increase their awareness and concern for nature (85,71% met); 4) Educational in which there is a mutual learning between visitors and community (100% met); 5) Its development be based on local community through agreement (20% met); 6) Empower and optimize participant and at the same time bring forth on going contribution to the local community (0% met), 7) To go by existing rules and law (100% met); 8) Consistently satisfy the visitors (50% met), 9) Being marketed and promoted openly and accurately to meet expectation – that is a marketing responsibility (100% met). Generally the result from comparison between ecotourism program with principal/criteria are as follows : from nine principles that already explained only the fifth and sixth principal whose its development less than 50%, based on those condition above it can be conclude that mangrove ecotourism development already fulfill the principal/criteria of national ecotourism. Important points of recommendations to the management are as follows; community participation; retributions, waste management; improvement of programs that are not working; and eco-tourism management under a solid institution.
Keywords: Evaluation; Eco-tourism, Tahura Ngurah Rai